Behavior of T-shaped CFST column to steel beam connection with U-shaped diaphragm. (November 2021) - Li, Binyang; Yang, Yuanlong; Liu, Jiepeng; Liu, Xianggang; Cheng, Yu; Chen, Yohchia Frank
Abstract: The connection between special-shaped concrete-filled steel tubular (CFST) column and steel beam is a particular concern to engineers. A novel U-shaped diaphragm connection is introduced in this paper to transfer the moment at beam ends in the frame with special-shaped CFST columns and steel beams. Five T-shaped CFST column to H-section steel beam connections were tested under low-cycle horizontal loading. U-shaped diaphragm was used as the connection to transfer loads from beam to joint panel zone. The experimental parameters include the size of U-shaped diaphragm and the axial load ratio of column. Based on the experimental results, the strength, ductility and strain distribution of the connections were calculated. Test results show that the connection can develop plastic bending capacity in the beam, satisfying the design code requirements of America, Great Britain, and China. Furthermore, a parametric analysis was conducted using the finite element method. The influences of U-shaped diaphragm size, tube thickness, and axial load ratio of column were analyzed. Based on the parametric analysis results, a mechanical model is proposed to calculate the yield strength and ultimate strength of U-shaped diaphragm connections. In conclusion, with a proper design, the T-shaped CFST column to H-section steel beam connection using the U-shaped diaphragm can be effectively used in practical applications. Highlights: Seismic loading tests are conducted on five large-scale connection specimens. Finite element model (FEM) is developed and verified with the experimental results. Parametric study using the FEM is carried out and mechanical model is proposed.